"Spopad knjig" - Vendramin, Valerija (Šolsko polje, 2006)
The author first deals with some controversies that are relevant in the literary criticism of today and hence in education and the formation of the curriculum. One of them is the so called split between aesthetics and ideology, between "the old ways" and "the new ways", between "literature" and "culture". She tries to show on the one hand that such polarisation can be problematic, and, on the other, that the reorientation does challenge some traditional paradigms - in the forefront here is the canon of literary works and its most representative author, W. Shakespeare, as a metaphor for the concepts of authorship, greatness, high vs. low culture etc. She then elaborates on the problematization of meaning-making and our social realities.Finally, she presents some theoretical work of approaching the concept of canon.
Keywords: literatura; literature; kultura; culture; književna vzgoja; curriculum; kurikulum; branje; literacy; pismenost; kanon